The other law in Lima, hora Cero by Enrique Congrains - Gamarra Orellana, Eduardo (2023)
This essay analyses the social transformations produced by the phenomenon of migration during the 1950s in Lima, hora cero, by the Peruvian writer Enrique Congrains Martín, from a legal point of view. Following the thread of the development of a spontaneous law as a hypothesis, we verify in the narration the situations that reflect the creation of the «other law» by the migrants in the urban context.